2022
DOI: 10.1016/j.bbiosy.2022.100042
|View full text |Cite
|
Sign up to set email alerts
|

Engineered extracellular vesicles antagonize SARS-CoV-2 infection by inhibiting mTOR signaling

Abstract: Effective treatment approaches for patients with COVID-19 remain limited and are neither curative nor widely applicable. Activated specialized tissue effector extracellular vesicles (ASTEX) derived from genetically-enhanced skin fibroblasts, exert disease-modifying bioactivity in vivo in models of heart disease. Here we report that ASTEX antagonizes SARS-CoV-2 infection and its pathogenic sequelae: In human lung epithelial cells exposed to SARS-CoV-2, ASTEX is cytoprotective and antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Clinical trials of antifibrotic therapies to limit/prevent pulmonary fibrosis for post-COVID patients are currently in progress; however, lung transplantations may be performed for fibroproliferative lung disease after ARDS due to COVID-19 [13]. ASTEX (activated specialized tissue effector extracellular) vesicles are cytoprotective and antiviral in human lung epithelial cells subjected to SARS-CoV-2 [66][67][68]. It inhibits SARS-CoV-2 infection and its pathogenic consequences by suppressing mTOR signaling, which in turn alters the transcriptome of infected cells [66][67][68].…”
Section: Clinical Management Of Covid-19 Long-haulersmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials of antifibrotic therapies to limit/prevent pulmonary fibrosis for post-COVID patients are currently in progress; however, lung transplantations may be performed for fibroproliferative lung disease after ARDS due to COVID-19 [13]. ASTEX (activated specialized tissue effector extracellular) vesicles are cytoprotective and antiviral in human lung epithelial cells subjected to SARS-CoV-2 [66][67][68]. It inhibits SARS-CoV-2 infection and its pathogenic consequences by suppressing mTOR signaling, which in turn alters the transcriptome of infected cells [66][67][68].…”
Section: Clinical Management Of Covid-19 Long-haulersmentioning
confidence: 99%
“…ASTEX (activated specialized tissue effector extracellular) vesicles are cytoprotective and antiviral in human lung epithelial cells subjected to SARS-CoV-2 [66][67][68]. It inhibits SARS-CoV-2 infection and its pathogenic consequences by suppressing mTOR signaling, which in turn alters the transcriptome of infected cells [66][67][68].…”
Section: Clinical Management Of Covid-19 Long-haulersmentioning
confidence: 99%
“…Furthermore, it has been shown that COVID-19 infected patient tissues and epithelial cells exhibit the abnormally activated mTOR signaling pathway, as evidenced by increased levels of phosphorylated 4E-BP1, AKT, S6K1 and mTOR (Appelberg et al, 2020;Mullen et al, 2021), suggesting the relevance of mTOR signaling activity and SARS-CoV-2 infection. More importantly, small molecule inhibitors targeting AKT and mTOR and engineered extracellular vesicles encapsulated microRNA targeting mTOR are able to significantly antagonize SARS-CoV-2 infection (Ibrahim et al, 2022), highlighting that inhibition of mTOR represents a feasible strategy for preventing COVID-19 (Basile et al, 2022).…”
Section: Mechanistic Target Of Rapamycin and Viral Skin Infectionmentioning
confidence: 99%
“…Moreover, the mechanistic target of the rapamycin (mTOR) pathway is the innermost regulator of cell growth, proliferation, metabolism and survival [ 54 ]. This pathway is a member of the protein kinases that senses both extracellular and intracellular regulatory signals to manage autophagy, the expression of inflammatory genes and organelle biogenesis [ 54 ].…”
Section: Growth Differentiation Factor 15 and Inflammatory Pathways I...mentioning
confidence: 99%
“…Moreover, the mechanistic target of the rapamycin (mTOR) pathway is the innermost regulator of cell growth, proliferation, metabolism and survival [ 54 ]. This pathway is a member of the protein kinases that senses both extracellular and intracellular regulatory signals to manage autophagy, the expression of inflammatory genes and organelle biogenesis [ 54 ]. It has been shown that the mTOR pathway is activated during the SARS-CoV-2 infection, and involved in the transcription and mRNA translation of the SARS-CoV-2 particles [ 55 ].…”
Section: Growth Differentiation Factor 15 and Inflammatory Pathways I...mentioning
confidence: 99%